Cryopreserved Placental Derivatives Improve Quality of Life and Behavioral Responses in Mice with Chemotherapy-Induced Ovarian Failure - Shevchenko, Mariіa; Mykhalchuk, Tetyana; Prokopіuk, Olga; Karpenko, Volodymyr; Prokopіuk, Volodymyr (Problems of Cryobiology and Cryomedicine, 2023)
Probl Cryobiol Cryomed 2023; 33(4): 274–279